Profil Persepsi Siswa terhadap Konsep Materi Himpunan pada Siswa SMP Kelas VII - Petrus Gelang; Kristoforus Djawa Djong; Irmina Veronika Uskono (Universitas Muria Kudus, 2020)
The purpose of this study was to determine the profile of students' perceptions of the concept of set material in seventh grade students of junior high school. The type of research used is descriptive qualitative. The subjects in this study were two seventh grade students of one junior high school in Kupang City with a high level of ability. Data collection is done by providing problem solving tasks (TPM), interviews and triangulation. Data analysis techniques used are data reduction, data presentation and conclusion drawing. In the first indicator, absorption, the results of the study show that the JW and VO subjects can mention information that is known in the TPM problem and mention what is asked in the matter of the TPM. In the second indicator, understanding or understanding, JW and VO subjects can understand how to solve TPM problems and mention the knowledge used to solve TPM problems. In the third indicator, evaluation or assessment, JW and VO subjects can solve problems and are able to explain the steps in solving TPM problems. Thus it can be concluded that both of subjects are able to fulfill all three indicators of perception